1991
DOI: 10.1136/oem.48.6.404
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory findings among ironworkers: results from a clinical survey in the New York metropolitan area and identification of health hazards from asbestos in place at work.

Abstract: Diseases associated with asbestos are prevalent in the construction trades primarily as the result of the previously widespread use of insulation materials containing asbestos in the building industry. Workers in metal related trades, who are employed at construction sites, but who do not routinely use such materials in their work, may also be at risk for asbestos hazards. To assess such risk, a clinical survey was conducted on 869 ironworkers from the New York metropolitan area. A high prevalence of abnormali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
3
5
0
1
Order By: Relevance
“…The lung function parameters most frequently studied with reference to asbestos-induced pleural lesions are TLC, FVC, and FEV 1 . In agreement with our conclusions, an effect of asbestos-induced pleural lesions on these parameters has been reported by many authors (8,(15)(16)(17)(18)(19)(20). Nevertheless, other authors (11,13,21) have not found a poorer lung function in the presence of pleural lesions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The lung function parameters most frequently studied with reference to asbestos-induced pleural lesions are TLC, FVC, and FEV 1 . In agreement with our conclusions, an effect of asbestos-induced pleural lesions on these parameters has been reported by many authors (8,(15)(16)(17)(18)(19)(20). Nevertheless, other authors (11,13,21) have not found a poorer lung function in the presence of pleural lesions.…”
Section: Discussionsupporting
confidence: 93%
“…DLCO impairment was associated with parenchymal fibrosis. Nor did we find any significant effect of pleural lesions on FEF 25-75 or FEF 75 , as reported by Fischbein et al (20), Kilburn & Warshaw (23), and Hillerdal et al (24). Nevertheless, we showed that parenchymal fibrosis has a significant effect on these parameters.…”
Section: Discussionsupporting
confidence: 61%
“…This was especially apparent for pleural thickening but, even for asbestosis that has a marked dose±response behaviour [Peto, 1978;Nicholson et al, 1982], latency time showed a stronger association. The same ®ndings were shown in a number of asbestos exposed workforces [Fischbein et al, 1991;Lilis et al, 1991;Jakobsson et al, 1995]. The assumption of a linear scale for the reported exposure in the different jobs in the A/C plant for deriving cumulative exposure might have been wrong.…”
Section: Discussionmentioning
confidence: 73%
“…Bourbeau et al [1990], reported the association of pleural thickening with SOB, but ORs were signi®cant only for SOB in strenuous exertion, possibly because of the small number of subjects in the group. Other large asbestos-exposed cohorts showed that the presence of pleural thickening was also associated with SOB [Broderick et al, 1991;Fischbein et al, 1991;Lilis et al, 1991]. In one of the cohorts, the association was signi®cant only with added asbestosis [Lilis et al, 1991].…”
Section: Discussionmentioning
confidence: 94%
“…Pleural plaques are considered to be a relatively sensitive indicator of asbestos exposure in the general population. Their prevalence increases at lower doses than the prevalence of small irregular opacities and diffuse pleural thickening [Neuberger, 19891. Recent studies reported a marked preponderance of pleural over parenchymal abnormalities in workers who used asbestos-containing products in their jobs [Lilis et al, 1980;Sprince et al, 1985;Lundorf et al, 1987;Fischbein et al, 1991;Becklake, 19911. Pleural plaques with no other asbestos-related abnormalities were also observed in general population surveys in men engaged in occupations with intermittent exposure as well as in individuals who had only household or environmental asbestos exposure [Ohyagi et al, 1985;Hillerdal, 19911.…”
Section: Introductionmentioning
confidence: 99%